Effectiveness of ecologically safe disinfectants against Pseudomonas aeruginosa and the poultry main bacteriosis pathogens - Berezovskiy, Andriy; Fotina, Tetiana; Vashchyk, Yevheniia; Berezhnyi, Dmytro; Morozenko, Dmytro (ScienceRise: Biological Science, 2022)
The aim: study of the effectiveness of environmentally safe disinfectants against P. aeruginosa and pathogens of the main bacteriosis of poultry at test facilities. Materials and methods. To study the antimicrobial action of the investigated disinfectants against a mixture of epizootic cultures of E. coli, P. aeruginosa, S. aureus, S. typhimurium, isolated from poultry, bacteriological studies were carried out on test objects: galvanized iron, wooden bars (painted and unpainted), red brick, cutouts from plaster, size 10 × 10 cm. Results. The working solutions of the new disinfectant "Dezsan" were studied in comparison with the control agents: "Virocid" and "Bi-dez" at a concentration of 0.01; 0.1; 0.25; 0.5; 1; 1.5 % in relation to suspension cultures of E. coli, P. aeruginosa, S. aureus, S. typhimurium. In this case, it was established, that the "Dezsan" agent showed an antimicrobial effect on rough test objects after exposure for 3 hours at a concentration of 0.1 %, and at a concentration of 0.25 % - for 1 hour. On smooth surfaces, the agent neutralized bacterial cultures at a concentration of 0.1 % after exposure for 1 hour. The preparation "Bi-dez" at a concentration of 0.25 % was effective on smooth surfaces after exposure for 1 hour, on rough surfaces (brick, plaster) - at a concentration of 0.5 % after exposure for 3 hours or more. The working solution of 1 % concentration neutralized bacterial cultures on all types of surfaces after exposure for 1 hour or more. "Virocid" agent after exposure for 1 hour neutralized bacterial cultures on smooth surfaces in concentrations of 0.25 % and higher; on rough surfaces, the growth of cultures was not detected when using a 0.5 % solution. Conclusions. Environmentally safe disinfectants "Dezsan" and "Shumerske sryblo" compared to the control ones ("Bi Dez" and "Virotsid") show an active antimicrobial effect at a concentration of 0.25 % and 3 %, respectively, against the suspension of epizootic cultures of E. coli, P. aeruginosa, S. aureus and S. typhimurium on different types of production surfaces, which justifies the feasibility of their use based on the principle of rotation of disinfectants for the prevention of bacterial pseudomonosis of poultry